Student- centred learning in the Liepaja University - Neimane, Ilma; Rupeika, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The idea about student focused higher education has been actualizped during the meeting of European ministers of Education and Science at Levene Kommunike in 2009, where higher education priorities in Europe were determined. Changing the role of student psychologically and economically as well to the student focused higher education represents obtaining the study course subbordinating it to achieved results not vice versa.. During the new study model the student becomes the partner of the teacher in case if he/she understands his/her rights, he/she is listened to and there is a possibility to achieve the identified goals and challenges. University of Liepaja has started to develop the following approach in study process.